Executive Board Progress Report to the IMFC on the Reform of Fund Governance. (Policy Papers; Policy Paper ;, 2010)
At its most recent meeting in April 2010, the IMFC pledged to complete the 14th General Review of Quotas before January 2011. This follows an earlier call by G-20 Leaders and the IMFC to bring forward the deadline for completing the 14th Review by two years as part of the multilateral response to the global financial crisis and the recognized need to enhance the Fund's legitimacy and effectiveness.